New constraints on Ganymede's hydrogen corona: Analysis of Lyman-α emissions observed by HST/STIS between 1998 and 2014. (15th November 2017) - Alday, Juan; Roth, Lorenz; Ivchenko, Nickolay; Retherford, Kurt D.; Becker, Tracy M.; Molyneux, Philippa; Saur, Joachim
Abstract: Far-ultraviolet observations of Ganymede's atmospheric emissions were obtained with the Space Telescope Imaging Spectrograph (STIS) onboard of the Hubble Space Telescope (HST) on several occasions between 1998 and 2014. We analyze the Lyman- α emission from four HST campaigns in order to constrain the abundance and variation of atomic hydrogen in Ganymede's atmosphere. We apply a forward model that estimates surface reflection and resonant scattering in an escaping corona of the solar Lyman- α flux, taking into account the effects of the hydrogen in the interplanetary medium. The atmospheric emissions around Ganymede's disk derived for the observations taken between 1998 and 2011 are consistent with a hydrogen corona in the density range of (5–8) × 10 3 cm −3 at the surface. The hydrogen density appears to be generally stable in that period. In 2014, Ganymede's corona brightness is approximately 3 times lower during two observations of Ganymede's trailing hemisphere and hardly detectable at all during two observations of the leading hemisphere. We also investigate extinction of Ganymede's coronal emissions in the Earth's upper atmosphere or geocorona. For small Doppler shifts, resonant scattering in the geocorona of the moon corona emissions can effectively reduce the brightness observed by HST. In the case of the 2014 leading hemisphere observations, an estimated extinction of 80% might explain the non-detection of Ganymede's hydrogen corona. Geocoronal extinction might also explain a previously detected hemispheric difference from Callisto's hydrogen corona. Highlights: Analysis of nine sets of H Lyman-α images of Ganymede made by the Hubble Space Telescope. Ganymede's H corona is constantly present at a similar level over more than a decade. Extinction in the Earth's geocorona can prevent the detection of planetary H coronae.